Making Policy Move : Towards a Politics of Translation and Assemblage - Clarke, John, 1950- (Book collections on Project MUSE., 2015)
Responding to the increasing interest in the movement of policies between places, sites and settings, this book presents a critical alternative to approaches centred on ideas of policy transfer, dissemination or learning. It argues that treating policy as an active process of 'translation', in which policies are interpreted, inflected and re-worked as they change location, is of critical importance for studying policy. The book provides an exciting and accessible analytical and methodological foundation for studying policy in this way.--Resume de l'editeur.